Hypertension in Pregnancy: Diagnosis, Blood Pressure Goals, and Pharmacotherapy: A Scientific Statement From the American Heart Association. Issue 2 (15th December 2021) - Garovic, Vesna D.; Dechend, Ralf; Easterling, Thomas; Karumanchi, S. Ananth; McMurtry Baird, Suzanne; Magee, Laura A.; Rana, Sarosh; Vermunt, Jane V.; August, Phyllis; ,
Abstract : Supplemental Digital Content is available in the text. Abstract : Hypertensive disorders of pregnancy (HDP) remain one of the major causes of pregnancy-related maternal and fetal morbidity and mortality worldwide. Affected women are also at increased risk for cardiovascular disease later in life, independently of traditional cardiovascular disease risks. Despite the immediate and long-term cardiovascular disease risks, recommendations for diagnosis and treatment of HDP in the United States have changed little, if at all, over past decades, unlike hypertension guidelines for the general population. The reasons for this approach include the question of benefit from normalization of blood pressure treatment for pregnant women, coupled with theoretical concerns for fetal well-being from a reduction in utero-placental perfusion and in utero exposure to antihypertensive medication. This report is based on a review of current literature and includes normal physiological changes in pregnancy that may affect clinical presentation of HDP; HDP epidemiology and the immediate and long-term sequelae of HDP; the pathophysiology of preeclampsia, an HDP commonly associated with proteinuria and increasingly recognized as a heterogeneous disease with different clinical phenotypes and likely distinct pathological mechanisms; a critical overview of current national and international HDP guidelines; emerging evidence that reducing blood pressure treatment goals in pregnancy may reduce maternal severe hypertension without increasing the risk of pregnancy loss, high-level neonatal care, or overall maternal complications; and the increasingly recognized morbidity associated with postpartum hypertension/preeclampsia. Finally, we discuss the future of research in the field and the pressing need to study socioeconomic and biological factors that may contribute to racial and ethnic maternal health care disparities.